The Role of MMP-9 and VEGF in the Invasion State of Bladder Urothelial Carcinoma - Novalia Chumaladewi Guntarno; Anny Setijo Rahaju; Nila Kurniasari (The Indonesian Biomedical Journal, 2021)
BACKGROUND: Bladder cancer is the tenth-most common cancer in worldwide and the majority are urothelial carcinomas. The depth of invasion plays important role in the prognostic and therapeutic factor in urothelial carcinomas. The expression of vascular endothelial growth factor (VEGF) and matrix metalloproteinase-9 (MMP-9) may associated with the progression of bladder carcinoma, such as depth of invasion. In this study, the correlation between these two markers in urothelial bladder carcinoma invasion will be analyzed.METHODS: An analytical observational research with cross-sectional were conducted on 54 formalin fixed paraffin-embedded tissue from radical cystectomy (RC) which were diagnosed as bladder urothelial carcinoma at the Anatomical Pathology Laboratory of Dr. Soetomo Academic Hospital, Surabaya and divided based on the T stage were immunostained using VEGF and MMP-9 monoclonal antibodies. The difference of VEGF and MMP-9 expression in T stage of bladder urothelial carcinoma were analyzed using Kruskal-Wallis and Anova test, the correlation between VEGF and MMP-9 expression in various T stage of bladder urothelial carcinoma were analyzed using Spearman test. RESULTS: This study showed no significant difference of VEGF expression among T stage of bladder urothelial carcinoma (p>0.05) but there was significant difference of MMP-9 expression in T stage of bladder urothelial carcinoma (p=0.043). There was a correlation between VEGF and MMP-9 in various T stage of bladder urothelial carcinoma (rs= 0.50, p=0.001).CONCLUSION: The significant correlation of VEGF and MMP-9 expression in bladder urothelial carcinoma may prove the synergistically role of both proteins in tumor invasion by MMP-9 degradation extracellular matrix.KEYWORDS: urothelial carcinoma, VEGF, MMP-9, T stage